Quantum chemical study on surface complex structures of phosphate on gibbsite - Luengo, Carina Vanesa (2015)
Quantum mechanics calculations based on the density functional theory (DFT) were used to identify phosphate surface complexes on gibbsite at low and high pH. The different phosphate species were represented using the Al6(OH)18(H2O)6 cluster model considering four different geometries: monodentate mononuclear (Pmm), monodentate binuclear (Pmb), bidentate mononuclear (Pbm) and bidentate binuclear (Pbb). The corresponding adsorption reactions were modelled via ligand exchange between phosphate species and surface functional groups (hydroxyls and protonated hydroxyls at high and low pH, respectively). The theoretical results indicate that phosphate surface complexes are thermodynamically more favored at acid pH, in agreement with experimental evidences. The first step in these reactions, i.e., the generation of required aluminum vacant sites, was predicted to be particularly favorable when singly coordinated aquo groups are released. Stretching and bending vibrational frequencies associated with the different surface structures were calculated at both pH conditions. The corresponding values at low pH were found to be shifted to higher frequencies with respect to those ones at high pH. ATR-FTIR studies were also carried out. The resulting spectra are dominated by a strong band within the 800?840 cm-1 interval due to P?OH stretching modes. The corresponding peak appearing around 820 cm_1 at high pH is shifted to lower frequencies with respect to the position at low pH, a tendency well predicted by DFT calculations.